Implementation of Deep Learning in the Digital Age through Training and Mentoring Programs in Cluster IV Minomartani - Kawuryan, Sekar Purbarini; Adi, Banu Setyo; Mujinem, Mujinem; Rochmah, Evy Nur; Kurniawati, Kurniawati; Wismoko Putri, Raudya Setya (Universitas Pahlawan Tuanku Tambusai, 2025)
Basic education in Indonesia still faces challenges, particularly in literacy, numeracy, and higher-order thinking skills. One-way learning, dominated by teachers as sources of information, is one of the causes of low student understanding. This community service program aims to improve the quality of learning through the implementation of a deep learning approach based on the principles of mindful, meaningful, and joyful learning. The target group is elementary school teachers in Cluster IV Minomartani, Sleman. The methods used include training, mentoring in the development of technology-based teaching materials, and reflection on learning implementation. The training and mentoring activities for the implementation of deep learning in the digital era carried out in Cluster IV Minomartani, Sleman, demonstrated an increase in teachers' understanding and skills in designing and implementing learning based on critical, collaborative, creative thinking, and effective communication. Based on initial and final evaluations, there was an average increase of 35% in understanding of deep learning concepts. In addition, 90% of participants were able to integrate digital technology into the learning process more innovatively, such as using interactive platforms, digital media, and project-based learning strategies.